Evaluation of The Vertebral Artery Using Color Duplex Sonography in Patients with Vertebrobasilar Insuffiency Symptoms (Annals of Medical Research, 2021)
None
Keywords: Vertebrobasilar insuffiency, Vertebral artery, Flow velocity, Flow volume, Doppler.